Correlation between Blood Glucose Level and Anthropometric Measurements among University Students at the University of Tripoli - Abdulwahb Al-Deib; Seham Eljali; Noor Elhuda Ehfied; Fardous Alallam (AlQalam Journal of Medical and Applied Sciences, 2024)
The detection of risk factors associated with type 2 diabetes mellitus (T2DM) at an earlier age may help reduce or even prevent the future outcomes of this disease. To date, there has been no research conducted on university students regarding associated risk factors such as being overweight or obese in Libya. The aim of this study was to determine any correlation between serum glucose level and anthropometric measurements, age and family history of T2DM in students of the University of Tripoli. A cross-sectional study involving a survey questionnaire, anthropometric measurement and blood glucose levels taken from 246 University students (aged 18-43). Recruitment was carried out from July 15 to August 1, 2024 at the research laboratory in the Faulty of Medical Technology at the University of Tripoli. The Pearson correlation test showed a positive correlation between the level of blood glucose and hip circumference [r= 0.139, P= 0.029]. The only other two risk factors that were close to the level of statistically significance were weight [r= 0.115, P= 0.071] and BMI [r= 0.117, P= 0.067]. T2DM might be prevented or mitigated by encouraging young adults in particular to keep hip circumference in the normal range. الكشف المبكر قد يساعد في اكتشاف عوامل الخطر المرتبطة بمرض السكري من النوع الثاني، قد يساعد في تقليل أو حتى منع النتائج المستقبلية لهذا المرض. حتى الآن، لم يتم إجراء أي بحث على طلاب الجامعات فيما يتعلق بعوامل الخطر المرتبطة مثل زيادة الوزن أو السمنة في ليبيا. . كان الهدف من هذه الدراسة تحديد أي ارتباط بين مستوى الجلوكوز في المصل والقياسات الأنثروبومترية والعمر والتاريخ العائلي لمرض السكري من النوع الثاني (2) لدى طلاب جامعة طرابلس.تم إجراء دراسة مقطعية تتضمن استبيانً وقياسً أنثروبومتريًا ومستويات السكر في الدم مأخوذة من 246 طالبًا جامعيًا (تتراوح أعمارهم بين 18 و 43 عامًا). تم تجميع العينات من الفترة من 15 يوليو إلى 1 أغسطس 2024 في مختبر الأبحاث التابع لكلية التقنية الطبية بجامعة طرابلس. أظهر اختبار ارتباط بيرسون وجود ارتباط إيجابي بين مستوى سكر الدم ومحيط الورك (r= 0.139, P = 0.029). كان عاملي الخطر الآخرين الوحيدين اللذين كانا قريبين من مستوى الأهمية الإحصائية هما الوزن (r= 0.115, P = 0.07). يمكن منع مرض السكري من النوع 2 أو التخفيف منه من خلال تشجيع الشباب على وجه الخصوص على الحفاظ على محيط الورك في النطاق الطبيعي